Precise Control of Perovskite Crystallization Kinetics via Sequential A‐Site Doping. Issue 42 (16th September 2020) - Qin, Minchao; Xue, Haibo; Zhang, Hengkai; Hu, Hanlin; Liu, Kuan; Li, Yuhao; Qin, Zhaotong; Ma, Junjie; Zhu, Hepeng; Yan, Keyou; Fang, Guojia; Li, Gang; et al.
Abstract: Two‐step‐fabricated FAPbI3 ‐based perovskites have attracted increasing attention because of their excellent film quality and reproducibility. However, the underlying film formation mechanism remains mysterious. Here, the crystallization kinetics of a benchmark FAPbI3 ‐based perovskite film with sequential A‐site doping of Cs + and GA + is revealed by in situ X‐ray scattering and first‐principles calculations. Incorporating Cs + in the first step induces an alternative pathway from δ‐CsPbI3 to perovskite α‐phase, which is energetically more favorable than the conventional pathways from PbI2 . However, pinholes are formed due to the nonuniform nucleation with sparse δ‐CsPbI3 crystals. Fortunately, incorporating GA + in the second step can not only promote the phase transition from δ‐CsPbI3 to the perovskite α‐phase, but also eliminate pinholes via Ostwald ripening and enhanced grain boundary migration, thus boosting efficiencies of perovskite solar cells over 23%. This work demonstrates the unprecedented advantage of the two‐step process over the one‐step process, allowing a precise control of the perovskite crystallization kinetics by decoupling the crystal nucleation and growth process. Abstract : The whole crystallization pathways and mechanism of two‐step‐fabricated perovskites are unveiled by in situ grazing‐incidence wide‐angle X‐ray scattering measurements and density functional theory calculations. Sequential A‐site doping of Cs + and GA + is found to alter the crystallization kinetics and improves the perovskite film morphology, giving rise to device efficiency as high as 23.5%.